High Voltage Pulser Based on a Tesla Transformerwith a Pulse-Forming Line Using an Open Ferrite Magnetic Core - Sinyakov A. N. Alexander Nikolaevich; Klimov A. I. Aleksey Ivanovich; Koval'chuk O. B. Oleg Borisovich; Rostov V. V. Vladislav Vladimirovich (Pulsed Power Technology, 2010)
Title screen